Islamic banking in Malaysia: cases and commentaries - Hassan, Rusni; Othman, Ahmad Azam; Mokhtar, Norlizah (The Malaysian Current Law Journal Sdn. Bhd., 2017)
Islamic banking in Malaysia has experienced an overwhelming boom, both in terms of the practice industry and legal development aspect. For stakeholders and practitioners, the practical concern centres, almost always, on the need to ensure that the products and practices abide by the Shariah and complies with Malaysian law. It is a known fact that at times, the Shariah principles did not come on all fours with the local laws and regulations, necessitating thereby much harmonisation effort for the two standards.